PENERAPAN VIDIO ANIMASI CUCI TANGAN PAKAI SABUN TERHADAP RESPON PADA ANAK DI SEKOLAH LUAR BIASA BUKITTINGGI - Rina Mariyana; Cory Febrina (LLDIKTI Wilayah X, 2021)
Special needs children have very limited access to health information, this is the cause of children susceptible to disease. Based on data from Unicef 2020, infectious disease mortality is 10%. The emergence of disease in children is one of the reasons for the lack of cleanliness of the child, which needs to be explained to children, how to wash hands properly, one of which is with animation media. The purpose of this research is to apply the animated video of washing hands with response to children in special schools Bukittinggi. This type of research uses a mixed methods study. The research was conducted in the city of Bukittinggi in March-October 2020. The population in this study were 34 extraordinary school children. The results showed that as much knowledge about knowledge in the use of hands with soap was mostly in the low category (73.5%) . Respondents The most attitudes in hand soap are in the category of disagree (79.4%). Most of the respondents' actions in washing their hands with soap were in the non-doing category (85.3%). The facilities and infrastructure for washing hands using soap are at most adequate (64.7%). where there is a significant correlation between children's knowledge and children's ability to wash their hands in 6 steps properly and correctly with p-value = 0.000 and 2 themes are obtained on qualitative methods of children's physiological responses and hand activity patterns